Effect of frailty on 6-month outcome after traumatic brain injury: a multicentre cohort study with external validation. Issue 2 (February 2022) - Galimberti, Stefania; Graziano, Francesca; Maas, Andrew I R; Isernia, Giulia; Lecky, Fiona; Jain, Sonia; Sun, Xiaoying; Gardner, Raquel C; Taylor, Sabrina R; Markowitz, Amy J; Manley, Geoffrey T; Valsecchi, Maria Grazia; et al.
Summary: Background: Frailty is known to be associated with poorer outcomes in individuals admitted to hospital for medical conditions requiring intensive care. However, little evidence is available for the effect of frailty on patients' outcomes after traumatic brain injury. Many frailty indices have been validated for clinical practice and show good performance to predict clinical outcomes. However, each is specific to a particular clinical context. We aimed to develop a frailty index to predict 6-month outcomes in patients after a traumatic brain injury. Methods: A cumulative deficit approach was used to create a novel frailty index based on 30 items dealing with disease states, current medications, and laboratory values derived from data available from CENTER-TBI, a prospective, longitudinal observational study of patients with traumatic brain injury presenting within 24 h of injury and admitted to a ward or an intensive care unit at 65 centres in Europe between Dec 19, 2014, and Dec 17, 2017. From the individual cumulative CENTER-TBI frailty index (range 0–30), we obtained a standardised value (range 0–1), with high scores indicating higher levels of frailty. The effect of frailty on 6-month outcome evaluated with the extended Glasgow Outcome Scale (GOSE) was assessed through a proportional odds logistic model adjusted for known outcome predictors. An unfavourable outcome was defined as death or severe disability (GOSE score ≤4). External validation was performed on data from TRACK-TBI, a prospective observational study co-designed with CENTER-TBI, which enrolled patients with traumatic brain injury at 18 level I trauma centres in the USA from Feb 26, 2014, to July 27, 2018. CENTER-TBI is registered with ClinicalTrials.gov, NCT02210221 ; TRACK-TBI is registered at ClinicalTrials.gov, NCT02119182 . Findings: 2993 participants (median age was 51 years [IQR 30–67], 2058 [69%] were men) were included in this analysis. The overall median CENTER-TBI frailty index score was 0·07 (IQR 0·03–0·15), with a median score of 0·17 (0·08–0·27) in older adults (aged ≥65 years). The CENTER-TBI frailty index score was significantly associated with the probability of an increasingly unfavourable outcome (cumulative odds ratio [OR] 1·03, 95% CI 1·02–1·04; p<0·0001), and the association was stronger for participants admitted to hospital wards (1·04, 1·03–1·06, p<0·0001) compared with those admitted to the intensive care unit (1·02, 1·01–1·03 p<0·0001). External validation of the CENTER-TBI frailty index in data from the TRACK-TBI (n=1667) cohort supported the robustness and reliability of these findings. The overall median TRACK-TBI frailty index score was 0·03 (IQR 0–0·10), with the frailty index score significantly associated with the risk of an increasingly unfavourable outcome in patients admitted to hospital wards (cumulative OR 1·05, 95% CI 1·03–1·08; p<0·0001), but not in those admitted to the intensive care unit (1·01, 0·99–1·03; p=0·43). Interpretation: We developed and externally validated a frailty index specific to traumatic brain injury. Risk of unfavourable outcome was significantly increased in participants with a higher CENTER-TBI frailty index score, regardless of age. Frailty identification could help to individualise rehabilitation approaches aimed at mitigating effects of frailty in patients with traumatic brain injury. Funding: European Union, Hannelore Kohl Stiftung, OneMind, Integra LifeSciences Corporation, NeuroTrauma Sciences, NIH-NINDS–TRACK-TBI, US Department of Defense.